Toxic waste minimization in the printed circuit board industry - Nunno, T. (Noyes Data Corp., 1988)
Presents information on waste minimization practices in the printed circuit board and semiconductor manufacturing industries. Case studies conducted at six facilities evaluated the technical, environmental and cost impacts associated with the implementation of technologies for reducing the volume and toxicity of printed-circuit-board metals-containing sludges and solvent wastes.
Keywords: Printed circuits industry -- Waste minimization -- Evaluation.; Printed circuits industry -- Waste minimization -- Case studies.; Semiconductor industry -- Waste minimization -- Evaluation.; Semiconductor industry -- Waste minimization -- Case studies.; elektronické knihy; electronic books